2013
DOI: 10.1016/j.ahj.2013.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Fractional flow reserve versus angiography in guiding management to optimize outcomes in non–ST-elevation myocardial infarction (FAMOUS-NSTEMI): Rationale and design of a randomized controlled clinical trial

Abstract: BackgroundIn patients with acute non–ST-elevation myocardial infarction (NSTEMI), coronary arteriography is usually recommended; but visual interpretation of the angiogram is subjective. We hypothesized that functional assessment of coronary stenosis severity with a pressure-sensitive guide wire (fractional flow reserve [FFR]) would have additive diagnostic, clinical, and health economic utility as compared with angiography-guided standard care.Methods and designA prospective multicenter parallel-group 1:1 ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Furthermore, this is a study of stable patients only and takes no account of the potential benefit of routine FFR in an ACS population, a question that is being addressed by the Fractional Flow Reserve Versus Angiography in Guiding Management to Optimise Outcomes in Non-ST-Segment-Elevation Myocardial Infarction (FAMOUS) study. 25 Therefore, we do not know from this study what effect FFR would have if used in this way in a consecutive all-comers group of patients. Third, several common patterns of CAD seen routinely at diagnostic angiography are poorly represented in this study population, including chronic total occlusions, left main stem lesions, and very diffusely diseased small vessels.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, this is a study of stable patients only and takes no account of the potential benefit of routine FFR in an ACS population, a question that is being addressed by the Fractional Flow Reserve Versus Angiography in Guiding Management to Optimise Outcomes in Non-ST-Segment-Elevation Myocardial Infarction (FAMOUS) study. 25 Therefore, we do not know from this study what effect FFR would have if used in this way in a consecutive all-comers group of patients. Third, several common patterns of CAD seen routinely at diagnostic angiography are poorly represented in this study population, including chronic total occlusions, left main stem lesions, and very diffusely diseased small vessels.…”
Section: Discussionmentioning
confidence: 98%
“…Fractional flow reserve is of great benefit in these situations due to the lack of noninvasive imaging prior to coronary angiography, unlike stable CAD. An ongoing multicenter randomized trial, Fractional Flow Reserve Versus Angiography in Guiding Management to Optimize Outcomes in Non–ST‐Elevation Myocardial Infarction (FAMOUS‐NSTEMI) is evaluating the feasibility of FFR measurement in NSTEMI and the influence of FFR disclosure on treatment decisions and health and economic outcomes …”
Section: Applications For Fractional Flow Reserve In Coronary Artery mentioning
confidence: 99%
“…No cases of adverse drug reactions related to the use of adenosine were recorded. The FAMOUS-NSTEMI [10,11] trial was created on the basis of the FAME trial [3], with the main differences seen in the type of patients who took part in the study (NSTEMI vs. CAD) as well as the degree of stenosis which was assessed (lesions ≥ 30% vs. ≥ 50%) [10,11]. A sub-study of FAMOUS-NSTEMI [10,11] compared FFR results with perfusion-magnetic resonance imaging (MRI) studies, and confirmed the diagnostic significance of FFR in stable patients with NSTEMI.…”
Section: Ffr-guided Vs Angiographic-guided Management In Acsmentioning
confidence: 99%
“…The FAMOUS-NSTEMI study compared angiographic assessment with FFR measurements with regards to determining further treatment in non-compromised patients with NSTEMI [10,11]. Patients were randomly assigned into one of three groups: coronary artery bypass graft (CABG), PCI or conservative treatment.…”
Section: Ffr-guided Vs Angiographic-guided Management In Acsmentioning
confidence: 99%
See 1 more Smart Citation